DEVELOPMENT OF ENGLISH LISTENING CONVERSATION LEARNING MEDIA THROUGH INTRODUCTION TO BATIK MOTIVES BASED ON MOBILE AUGMENTED REALITY - Riski Sulistiyaningsih; Ichwan Kurniawan; Nur Fadhilah; Deni Syamsu Rakhmanto (Universitas Islam Nahdlatul Ulama Jepara, 2021)
The use of Digital audio video learning media has been implemented in teaching learning process at STMIK Widya Pratama Pekalongan. Nevertheless student still has difficulty in listening conversation. Based on the problem statement this research is aimed at developing the English lesson learning media through batik motif introduction with mobile augmented reality based for STMIK Widya Pratama Pekalongan student. The ADDIE (Analyze, Design, Develop, Implement, Evaluate), method is used in this learning media development research, all stage of method has completed and created the English learning media with mobile augmented reality technology based. The result of the research yielded by UAT (User Acceptance Test) stated that the English Learning media development through batik motif introduction with mobile augmented reality based may be implemented in English teaching learning process as well as supporting the explanation on the English materials. Nevertheless, the material discussion is focussing only on English structure.